INFLUENCE OF INVESTMENT DECISIONS, FUNDING DECISIONS, PROFIT MARGINON THE VALUE OF THE COMPANY IN AUTOMOTIVE COMPANIES IN THE PERIOD 2017-2022 - Himmatul Ulya; Suhendi; Mesra B (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The purpose of this research is to determine and analyze the partial and simultaneous influence of investment decision variables, funding decisions, and net profitable margin on company value in automotive companies for the 2017-2022 period. The population is all members and parts of research subjects who have certain characteristics and information needed by researchers for survey needs (Stockemer, 2019). The population in this study were 42 automotive sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2017-2022. The criteria for determining the sample companies in this research were Automotive Sector Manufacturing companies registered on the IDX during the 2017-2022 period, Automotive Sector Manufacturing companies that published financial reports for the 2017-2022 period, and Automotive Sector Companies that published annual reports for the 2017-2022 period. 2022. The results obtained from this research show that: Investment decisions partially have a positive and significant effect on company value in Automotive companies listed on the Indonesia Stock Exchange, Investment Decisions partially have a positive and significant effect on company value in Automotive companies listed on the Indonesian Stock Exchange Effect, Net profit margin partially has a positive and significant effect on company value in Automotive companies listed on the Indonesian Stock Exchange, and investment decisions, funding decisions, and profit margins simultaneously have a positive and significant effect on company value in Automotive companies listed on Indonesia stock exchange. The customized R square value of 0.488 can be called the coefficient of determination, this means that 0.488 (48.8%) of the company value can be obtained and explained by investment decisions, funding decisions and net profit margin while the remaining 51.2% (100% - 48, 8 % = 51.2%) explained by variables outside the model that were not studied.